Studi Kualitatif tentang Pengetahuan Lokal dalam Perawatan Mesin Kapal oleh Nelayan Tradisional di Atapupu Belu-NTT - Pereira Maia Pinto, Gaspar; Bilak Lopo, Elkana; Ronald Rohi, Jemssy (PT Yupin Felicitas Utama, 2025)
This study aims to explore the local knowledge possessed by traditional fishermen in Atapupu, Belu, East Nusa Tenggara (NTT) in ship engine maintenance. Using a qualitative approach, this study collected data through in-depth interviews, observations, and documentation studies. The results of the study indicate that local knowledge possessed by fishermen not only includes engine maintenance techniques, but also involves cultural and environmental aspects that influence maintenance practices. These findings are expected to contribute to the development of more sustainable fisheries policies and the preservation of local knowledge.